Molecular epidemiology of foot-and-mouth disease (review) - A. V. Scherbakov (Ветеринария сегодня)
Molecular epidemiological studies are an important tool for regional and global surveillance of foot-and-mouth disease (FMD). These tests are based on constantly progressing technologies of nucleic acid sequencing and phylogenetic analysis. The use of these technologies made it possible to assess the genetic diversity of the FMD virus, to analyze the evolution of the virus in the enzootic regions, and track the pathways of FMD epizootic and panzootic spread. Molecular epidemiological studies have shown that within the long-known seven serotypes of the FMD virus, there are numerous topotypes (geographical types), genetic lineages and sublineages. Usually, the foot-and-mouth disease virus of a certain topotype and genetic lineage evolves within a certain area, periodically causing regional epizootics. However, over the past 30 years, two FMD panzootics have occurred, invloving several continents. The first panzootic occurred in the late 1990s – early 2000s and was caused by O/ME-SA/PanAsia FMDV, and the second, caused by O/ME-SA/Ind-2001 virus, began in 2013 and continues to the present. The emergence of FMD panzootics is probably a consequence of the economic globalization. FMD is not enzootic in Russia, but sporadic outbreaks of this disease are periodically reported. Molecular epidemiological studies have shown that these outbreaks are caused by the infection introduction from neighboring Asian countries, mainly from China. The FMD virus, which has come to the Russian Federation from other countries, is characterized by great genetic diversity and belongs to three serotypes, five topotypes and eight genetic lineages: O/Cathay, O/ME-SA/PanAsia, O/SEA/Mya-98, O/ME-SA/Ind-2001, O/ME-SA/unnamed, A/Asia/Iran-05, A/Asia/Sea-97, Asia1/V. The results of molecular epidemiological studies are taken into account when vaccine strains are to be selected for preventive vaccination of livestock in FMD high-risk areas. The review is based on the analysis of 68 literature sources.